Elaboración de un plan de mantenimiento preventivo para el tren de laminación de productos pequeños (LPP) de la empresa NOVACERO S.A. Planta Lasso. - Muso Tibán, Cristian Fabricio (2018)
In NOVACERO S.A Company Lasso plant, currently it consists of two lines to manufacture profiles. “El Tren dos” which previously produced all the hot rolled profiles manufactured in its Lasso plant and el tren LPP (Laminate of small products), which replaced it in 2012 in the production of short profiles dimensions. “El tren LPP”, specializes in the manufacture of square bars and platens of different dimensions, which are marketed nationally and internationally. “El tren LPP”, previously worked with an inefficient heating furnace that produced excess pollution and poor performance in 2014, it was decided to replace it with induction furnaces, which increased its effectiveness and efficiency by 60%, which caused a greater supply. The production of “el tren LPP”, works 24 hours a day, from Monday to Friday in two rotating shifts, this generates an offer of around 20 -24 tons of finished product, when “el tren LPP” shows breakdowns it cause losses in its daily productivity losing market competitive as well as its responsibility, also of the fulfillment of productivity as a work area, for which the elaboration and implementation of a preventive maintenance plan in “el tren LPP” will be determined, which will reduce pauses due to equipment failures and prevent the them by breakdowns, bad calibrations, lack of lubrication, within the area, to optimize the production process and meet the potential demand. The maintenance plan will help the scheduled maintenance administration, through the monthly indicators that will be presented each month to the immediate boss detailing the index of failures during the month and making more emphasis on correcting the mistakes detected.